Dynamic capabilities and the entrepreneurial university: a perspective on the knowledge transfer capabilities of universities. (4th May 2019) - O'Reilly, Noel M.; Robbins, Peter; Scanlan, John
Abstract : In the knowledge economy, universities have a vital and growing role in supporting innovation and facilitating regional economic development through the addition of a 'third mission' of knowledge transfer activities to the core missions of teaching and academic research. Knowledge transfer capabilities appear to be influenced by the dynamic capabilities and culture of the host university. To date, knowledge transfer activities of universities have proven difficult to quantify with comparisons between institutions problematic. This paper addresses this gap in two ways. Firstly, the use of a ratio of published metrics gives greater insight into the relative degree of collaboration between universities and industry. Secondly, this research derives a measure of dynamic capabilities in Irish universities and correlates it with previously unpublished data on technology and knowledge transfer performance. The research finds a high correlation between universities with strong dynamic capabilities and their success in these dimensions of knowledge transfer. Keywords: entrepreneurial university; dynamic capabilities; knowledge transfer; innovation culture Dans l'économie de la connaissance, les universités ont un rôle essentiel et croissant l'innovation de soutien et en facilitant le développement économique régional par l'addition d'une 'troisième mission' des activités de transfert de la connaissance aux missions de noyau de l'enseignement et de la recherche scolaire. Les capacités de transfert de la connaissance semblent Átre influencées par les capacités et la culture dynamiques de l'universitéde centre serveur. Jusqu'à présent, les activités de transfert de la connaissance des universités ont prouvé difficile à mesurer avec des comparaisons entre les établissements problématiques. Ce document adresse cete space de deux manières. Premièrement, l'utilisation d'un rapport de la métrique éditée donne une plus grande analyse dans le degré relatif de collaboration entre les universités et l'industrie. Deuxièmement, cette recherche dériveune mesure de capacités dynamiques aux universités irlandaises et la corrèle avec desdonnées précédemment non publiées sur l'interprétation de transfert de technologie et deconnaissance. La recherche trouve une corrélation élevée entre les universités avec descapacités dynamiques fortes et leur succès dans ces dimensions de transfert de la connaissance.